Transfection of clMagR/clCry4 imparts MR-T2 imaging contrast properties to living organisms (E. coli) in the presence of Fe3+ by endogenous formation of iron oxide nanoparticles - Li, Nuan; Xue, Le; Mai, Xiaoli; Wang, Peng; Zhu, Chenzhuo; Han, Xiaofeng; Xie, Yuanyuan; Wang, Bin; Ge, Yuqing; Zhang, Yewei; Sun, Jianfei (Frontiers in Molecular Biosciences, 2023)
Rapid development of medical imaging, such as cellular tracking has increased the demand for ‘live’ contrast agents. This study provides the first experimental evidence demonstrating that transfection of the clMagR/clCry4 gene can impart magnetic resonance imaging (MRI) T2-contrast properties to living prokaryotic Escherichia coli (E. coli) in the presence of Fe3+ through the endogenous formation of iron oxide nanoparticles. The transfected clMagR/clCry4gene markedly promoted uptake of exogenous iron by E. coli, achieving an intracellular co-precipitation condition and formation of iron oxide nanoparticles. This study will stimulate further exploration of the biological applications of clMagR/clCry4 in imaging studies.